Three Weak Solutions for ($p(x)$,$q(x)$)-Biharmonic Problem with Hardy Weight with Two Parameters (Journal of Nonlinear Modeling and Analysis, 2025)
The focus of this study is on the existence of three solutions to($p(·)$, $q(·)$)-biharmonic operator with an $s(x)$-Hardy term under no-flux boundary conditions. Our method is based on the variational method and criticalpoint results.
Keywords: Variational method; singular problem; $p(x)$-biharmonic operator.